Multicultural Education in Indonesian Diaspora Families (Study Case: Gelin Community) - Anggraeni, Nur Najmi; Ustaadza, Laillatus Sholikhah; Komalasari, Komalasari (Educative: Jurnal Ilmiah Pendidikan, 2023)
This writing discusses multicultural education in Indonesian diaspora families in Türkiye. It aims to reveal the application of multicultural education in the Gelin community in Turkey as an attempt to present the identity as Indonesian and measure the understanding of Nationalism and tolerance in the families of the Gelincommunity in Turkey. This writing method uses qualitative research methods with sources Indonesian gelinwho are married to Turks and living in Turkey. The ups and downs of the application of multicultural education are passed in mixed marriages, gelins in Turkey have their own pattern regarding the application of multicultural educaion which they teach to their children. Although there are no official rules for the use of multicultural education, multicultural education is a way to help children from mixed marriages find their identities without being forced to side with two different nationalities.